Penerapan Teknologi Informasi dan Komunikasi di Kantor Redaksi HU Berita Cianjur - Nai Siti Aisiah (STISIP Widyapuri Mandiri Sukabumi, 2022)
Information and communication systems are interactions between data, humans and procedures that are supported by hardware, software, and braindware to provide a solution in the form of information that can be used to take a further decision, both short, medium and long term in an organization. With the existence of ICT will save costs in all aspects, labor, process, marketing, and managerial. This study aims to determine the application of ICT in the HU News Cianjur editorial office. The method used is participatory qualitative observation, the researcher acts as an observer and observes in order to observe things related to the main objectives of the study. The results showed that the editorial office of HU Berita Cianjur implemented modern and renewable ICT. This policy is to support the work process of all existing divisions, especially the editorial staff in terms of internet access which cannot be separated from the existing system and work procedures, especially the news distribution process from reporters to appearances. The results of preprinted products are sent to the printing company through supporting applications. Meanwhile, to regulate the regulation and distribution of news between desks, a server system is used using the main computer as a data center. In order to be able to connect between parties using the Local Areal Network (LAN) system, which is also used to transform company information, including the dissemination of policies or regulations. This step is part of the implementation of IT Governance, namely corporate governance that focuses on information technology systems as well as performance and risk management which includes computer resources. However, there are obstacles, namely the availability of facilities and infrastructure. The reason is that this infrastructure problem requires no small amount of money, so that the management is limited in allocating the budget for the development of this ICT-based infrastructure. Another obstacle is the inability of individuals to use it. The reason is, even though the communication facilities have been adequate with advanced technology, some have not been able to use them. In addition, obstacles from the application of ICT are also related to the individual's ability to communicate.